Main nutrients of the food supplements used by elderly and the benefits for health (Research, Society and Development, 2022)
In recent years, there has been a very significant growth in the use of food supplements. Concomitantly, the increase in life expectancy drives industries to develop products that are intended to complement the diet of the elderly, who represent a high percentage of individuals with nutritional deficiencies. There is a greater concern in nutritional issues, which raises scientific questions about the benefits and harms of the use of supplementation in aging. In this way, the present study aimed to verify the main nutrients present in food supplements relating the impact of their use by the elderly. A bibliographic survey was carried out in databases, seeking scientific articles preferably updated, using some descriptors such as aging, food supplements, nutrition for the elderly. The results obtained showed that the main nutrients present in food supplements are vitamins, minerals and proteins, which can bring several benefits, improving the quality of life of the elderly. Despite the numerous beneficial effects of food supplements, especially on the immune system and on the cognitive process, the toxic effects that excessive consumption can impact on the health of the elderly are opposed, and the rational use of these products is important.